Increased Medial Longitudinal Arch Mobility, Lower Extremity Kinematics, and Ground Reaction Forces in High-Arched Runners - Williams, D. S. Blaise (National Athletic Trainers Association, 2014)
CONTEXT: Runners with high medial longitudinal arch structure demonstrate unique kinematics and kinetics that may lead to running injuries. The mobility of the midfoot as measured by the change in arch height is also suspected to play a role in lower extremity function during running. The effect of arch mobility in high-arched runners is an important factor in prescribing footwear, training, and rehabilitating the running athlete after injury. OBJECTIVE: To examine the effect of medial longitudinal arch mobility on running kinematics, ground reaction forces, and loading rates in high-arched runners. DESIGN: Cross-sectional study. SETTING: Human movement research laboratory. PATIENTS OR OTHER PARTICIPANTS: A total of 104 runners were screened for arch height. Runners were then identified as having high arches if the arch height index was greater than 0.5 SD above the mean. Of the runners with high arches, 11 rigid runners with the lowest arch mobility (R) were compared with 8 mobile runners with the highest arch mobility (M). Arch mobility was determined by calculating the left arch height index in all runners. INTERVENTION(S): Three-dimensional motion analysis of running over ground. MAIN OUTCOME MEASURE(S): Rearfoot and tibial angular excursions, eversion-to-tibial internal-rotation ratio, vertical ground reaction forces, and the associated loading rates. RESULTS: Runners with mobile arches exhibited decreased tibial internal-rotation excursion (mobile: 5.6° ± 2.3° versus rigid: 8.0° ± 3.0°), greater eversion-to-tibial internal-rotation ratio (mobile: 2.1 ± 0.8 versus rigid: 1.5 ± 0.5), decreased second peak vertical ground reaction force values (mobile: 2.3 ± 0.2 × body weight versus rigid: 2.4 ± 0.1 × body weight), and decreased vertical loading rate values (mobile: 55.7 ± 14.1 × body weight/s versus rigid: 65.9 ± 11.4 × body weight/s). CONCLUSIONS: Based on the results of this study, it appears that runners with high arch structure but differing arch mobility exhibited differences in select lower extremity movement patterns and forces. Future authors should investigate the impact of arch mobility on running-related injuries.